MA SIZONG'S VIOLIN WORK IN CONTEXT ARTISTIC AND AESTHETIC TRENDS AND ARTISTIC DIRECTIONS OF THE TWENTIETH CENTURY - Li Yan Lun (International Journal of Innovative Technologies in Social Science, 2021)
The problem of synthesis of artistic and aesthetic directions of the XX century is considered in the violin music of the Chinese composer Ma Sitsong, whose creative path is outlined in the European, Chinese and American periods. Ma Sitsong was the first Chinese musician to study at the Paris Conservatory and adapt the modernist tendencies of Europe (Impressionism by C. Debussy; I. Stravinsky's search for the "Holy Spring", B. Bartok's neo-folklore). The principles of the latter resonated with Ma's intense reliance on the national Chinese firstborn. After returning to China, he admired the work of S. Prokofiev. Violin music (the first Chinese Concerto, Xinyan Rhapsody for Violin and Orchestra, Suiyuan Suite, Rondo №№1-2) showed a bright national beginning combined with neo-romantic tone and impressionistic sound recording. The mystical-religious figurative conceptosphere of the Tibet Suite is full of symbolic features. After emigrating to the United States, the composer turned to the native music of Taiwanese aborigines (Amei and Gaoshan Suites). Reproducing archaic images, Ma tends to Fauvism, primitive naivety and minimalism, continuing the line of I. Stravinsky, corresponding with the search for his contemporaries: O. Messian, J. Cram, J. Cage, T. Takemitsu, M. Skoryk. In works of the American period (Concerto for 2 violins, Rondo №№3-4, Sonata №3, Sonata for 2 violins solo) neoclassical, expressionist, urban features, elements of Westernization, jazz are felt. Ma Sitsong, as one of the founders of the national violin school, organically combines the diversity of world trends with a lasting reliance on Chinese folk music.